Dependência química e juventude: a carreira moral de jovens adictos em instituições de recuperação - Monteiro, Rita Maria Paiva (2010)
This dissertation aims at understanding actual intervention and reach of therapeutic practices (medical or religious) involving three private institutions that have establish to themselves the goal of recuperating chemically dependent persons considering as such individuals whose daily activities turn around consumption of one or more drugs rendering them useless by avoiding any other function. Chemically dependent persons who have contributed information to this research are positioned in the age range of 15 to 29 years old, are users of illegal drugs, and all of them are or have been committed to an institution. By exploring their discourses I try to identify possible interference of those practices as they affect those youngsters’ relation with drugs beside the impact caused by the institutional evaluation of their addiction. Others contributors to the research are health-related professionals and members of the clergy who are directly involved with the youngsters. I tried to use the youngsters’ discourse as a methodological tool in relation to their involvement with drugs and subsequent search by them of institutions that help addicts, besides observing and ethnographing the setting in an attempt to weave a “web of meanings” in Clifford Geertz’s perspective aiming at understanding a world that has received a legally scientific stamp and is seen by a construct of a set of social values as a “place” of transformation and recovery.